University Students’ Competencies and Character Qualities Developed in Design Thinking - Lim, Jin Wei; Tan, Daniel Eng Keng; Wong, Christine; Nur Hanani, Muhammad (INTI International University, 2018)
Design creativity" is now a popular trend to groom innovative people in problem solving. This study centered on the university students’ Social and Emotional Learning (SEL) towards Design Thinking approach to deliver a new or improved outcome (product or service). Questionnaires and feedback from students were employed to gather extensive data on students’ competencies and character qualities during the Design Thinking project. Key findings show that the university students are self-engaged in problem-solving activities based on real world scenarios. They appreciate communication and collaboration among group members and industrial experts. Design thinking harnesses students’ learning and real world experiences.